Getting to Know Democracy in the Primary School Environment - Annisa Rahmah Siregar (International Journal of Students Education, 2024)
Education is a need for everyone. From time to time, education always experiences developments in a better direction, such as the implementation of educational democracy in learning which carries the concept of giving students freedom to express opinions, express objections, and also have equal opportunities without any distinction in terms of ethnicity, race and class. This research aims to determine the application of educational democracy in the student learning process in elementary schools. This research uses a literature study method where information is obtained from journals, articles, and sites available on the web and analyzed using a qualitative approach using information analysis techniques through four stages, namely searching for information, reducing information, presenting information, and drawing conclusions. The research results show that students are currently not only used as learning objects but also as subjects who are involved in discussions during the learning process. Therefore, it is hoped that masters will be able to create a democratic learning environment for students. Educational democracy is realized in democratic school learning, namely by involving all parties such as teachers, students and other parties involved in education (Zahrawati B, 2018).